GAYA KEPEMIMPINAN DAN ETOS KERJA KEPALA MADRASAH HUBUNGANYA DENGAN KINERJA TENAGA KEPENDIDIKAN - Nifasri; Lestari, Ambar Sri; Nurhalimah, Mina (Department of Islamic Education Management, 2025)
The leadership style and work ethic of madrasah heads are very important in improving the performance of educational staff. This research aims to determine the relationship between the leadership style and work ethic of madrasah heads and the performance of educational staff in MAN throughout Bandung Regency. This research uses a quantitative descriptive method approach. The data analysis used is correlational analysis. The data source was obtained through distributing questionnaires to 43 MAN education staff throughout Bandung Regency. The results of research based on correlation tests that have been carried out can be concluded that there is a significant relationship between the leadership style and work ethic of madrasa heads and the performance of educational staff in MAN throughout Bandung Regency. Based on the coefficient of determination test in this research, a result of 0.204 was obtained, which means that the contribution of leadership style and work ethic variables to the performance of educational staff was 20.4%.